2018
DOI: 10.1016/j.tube.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

I3-Ag85 effect on phthiodiolone dimycocerosate synthesis

Abstract: The multiplicity of drug resistant Mycobacterium tuberculosis (Mtb) strains is a growing health issue. New therapies are needed, acting on new targets. The I3-Ag85 was already reported to reduce the amount of trehalose dimycolate lipid of the mycobacterial cell wall. This inhibitor of Ag85C increased the mycobacterial wall permeability. We previously showed that M. tuberculosis strains, even multi-drug resistant and extensively-drug resistant strains, can be susceptible to vancomycin when concomitantly treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This logic is followed in most studies, including intact PDIMs (Minnikin et al 1985c;Daffé and Lanéelle 1988;Daffé 1991;Onwueme et al 2005). However, some recent studies (Huet et al 2009;Rens et al 2018) have disregarded the existence of phthiocerol B and inappropriately used the abbreviation PDIM B for the wax based on phthiodiolone A! Overall rationalization of the nomenclature of members of the phthiocerol family has been proposed by Onwueme et al (2005).…”
Section: Phthiocerol Dimycocerosates (Pdims)mentioning
confidence: 99%
“…This logic is followed in most studies, including intact PDIMs (Minnikin et al 1985c;Daffé and Lanéelle 1988;Daffé 1991;Onwueme et al 2005). However, some recent studies (Huet et al 2009;Rens et al 2018) have disregarded the existence of phthiocerol B and inappropriately used the abbreviation PDIM B for the wax based on phthiodiolone A! Overall rationalization of the nomenclature of members of the phthiocerol family has been proposed by Onwueme et al (2005).…”
Section: Phthiocerol Dimycocerosates (Pdims)mentioning
confidence: 99%
“…MPV was well-documented alone or in relation to other inflammatory markers, such as CRP and ESR (erythrocyte sedimentation rate) in some chronic inflammatory disease to monitor the response to anti-inflammatory treatment [ 62 , 63 ]. Tozkoparan et al observed that the MPV decreased significantly with anti-TB treatment [ 64 ], while others found similar values between patients with PTB and healthy subjects [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated the prediction potential of CRP for treatment outcomes in PTB patients in combination with different inflammatory biomarkers, such as the pro-inflammatory chemokine, cytokine, or antimicrobial peptide [ 65 , 66 ]. Interferon gamma (IFN-g)-inducible protein 10 (IP-10) is a pro-inflammatory chemokine that has been evaluated for the diagnostic potential in TB, but the results are varied [ 24 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ag85 has a mycolyl transferase activity, which is needed for attachment of mycolic acids to arabinogalactan and the formation of cord factor (Kuo et al 2012). After the entry of M.tb into the cellular phagosome, the Ag85 complex inhibits the formation of phagolysosome and therefore, has a pivotal role in the intracellular pathogenesis of M.tb (Rens et al 2018). Consequently, members of the Ag85 complex can promote Th1 cell response to produce interferon-gamma (IFN-γ) and interleukin-2 (IL-2) cytokines (Huygen 2014).…”
Section: Introductionmentioning
confidence: 99%